The Role of the Indonesian Mosque Youth Communication Agency (BKPRMI) in Empowering Mosque-Based Communities in Labuhanbatu Regency - Ningrum, Widya Sari; Ritonga, Hasnun Jauhari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study examines the function of the Indonesian Mosque Youth Communication Board (BKPRMI) in the empowerment of mosque-based communities in the Labuhanbatu Regency, North Sumatra Province. The research method used is qualitative, i.e. research that produces data in the form of words or actions orally or in writing, the type of data used is primary data and secondary data in collecting data through observation and interview methods, and the Indonesian Mosque Youth Communication Board (BKPRMI) in empowering communities based on the Labuhanbatu mosque to empower and develop through programmes that are divided into four aspects: (1) the religious aspect; (2) the social aspect; (3) the economic aspect; and (4) the educational aspect. (3) through economic aspects by carrying out charity box management activities in mosques, optimising mosque courtyards for local community SMEs, forming BKPRMI business entities, and organising entrepreneurial training in collaboration with HIPMI (Iran).